Impact of Genetic Disorders in the Surgical Management of Congenital Heart Disease. Issue 2 (March 2023) - Stephens, Elizabeth H; Dearani, Joseph A; Connolly, Heidi M; Gleich, Stephen J; Deyle, David R; Johnson, Jonathan N
The congenital heart surgeon frequently encounters patients with various genetic disorders requiring surgical intervention. Although the specifics of the genetics for these patients and their families lie in the purview of specialists in genetics, the surgeon is well-served to be familiar with aspects of specific syndromes that impact surgical management and perioperative care. This aids in counseling families in expectations for the hospital course and recovery as well as can impact intraoperative and surgical management. This review article summarizes key characteristics for the congenital heart surgeon to be familiar with for common genetic disorders as they help coordinate care.